A comparative study of intra venous patient-controlled analgesia morphine and tramadol in patients undergoing major operation - Hassan, Shamsul Kamalrujan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2003)
Introduction: The success of major surgery depends partly on providing effective post-operative pain relief, which can be achieved by morphine administration via PCA system. Tramadol is a weak opioid analgesic, which act mainly on f..L-opioid receptor. The purpose of this study was to evaluate the effectiveness of intravenous patient-controlled analgesia (PCA) Tramadol in comparison with PCA Morphine in tenn of analgesic properties, sedation and other side effects such as nausea, vomiting and pruritus. Methods: A randomized, double-blinded study was conducted on 160 selected ASA I and II patients who were divided into two groups by a closed envelope technique. Following surgery, the PCA morphine (M) group (n=80) received a loading dose of 0.1 mglkg of intravenous morphine followed by I mg ( 1 mg/ml) of PCA infusion as required. The PCA tramadol (T) group (n=80) received a loading dose of 2.5 mg/kg of intravenous tramadol followed by 10 mg (10 mg/ml) ofPCA infusion as required. The lockout intervals for both groups were 10 minutes. None of the patients received baseline infusion. In the recovery room, patients were given oxygen via facemask and monitored for pain score according to Modified Pain Score, sedation scoreaccording to Ramsay Sedation Score, respiratory rate, nausea, vomiting, pruritus, blood pressure and pulse rate. Patients were evaluated at the end of 30 minutes in recovery room. After 4 hours, 24 hours and 48 hours post operation, patients were again evaluated in the ward. Results: Showed no difference in the demographic data between the two groups (p>0.05). The mean pain score in tramadol group at 30 minutes, 4 hours, 24 hours and 48 hours post operation were 1.32 ± 0.79, 1.04 ± 0.79, 0.35 ± 0.48 and 0.09 ± 0.33 respectively. Whereas, the mean pain score in morphine group at 30 minutes, 4 hours, 24 hours and 48 hours post operation were 1.35 ± 0.99, 1.14 ± 0.81, 0.40 ± 0.54 and 0.10 ± 0.34 respectively. There were no significant differences in the mean pain score between the t\vo groups at each duration of assessment (p>0.05). The mean sedation score in tramadol group at 30 minutes, 4 hours, 24 hours and 48 hours post operation were 0.90 ± 0.74, 0.56 ± 0.59, 0.08 ± 0.27 and 0.02 ± 0.16 respectively. Whereas, the mean sedation score in morphine group at 30 minutes, 4 hours, 24 hours and 48 hours post operation were 0.84 ± 0.70, 0.46 ± 0.64, 0.08 ± 0.27 and 0.01 ± 0.11 respectively. There were no significant differences in the mean sedation score between the two groups at each duration of assessment (p>0.05). There were also no significant differences between the two groups in the incidence of nausea, vomiting and pruritus.